Using European travellers as an early alert to detect emerging pathogens in countries with limited laboratory resources - Grais Rebecca; Guerin Philippe J; Rottingen John; Valleron Alain (BMC, 2007)
Abstract Background The volume, extent and speed of travel have dramatically increased in the past decades, providing the potential for an infectious disease to spread through the transportation network. By collecting information on the suspected place of infection, existing surveillance systems in industrialized countries may provide timely information for areas of the world without adequate surveillance currently in place. We present the results of a case study using reported cases of Shigella dysenteriae serotype 1 (Sd1) in European travellers to detect "events" of Sd1, related to either epidemic cases or endemic cases in developing countries. Methods We identified papers from a Medline search for reported events of Sd1 from 1940 to 2002. We requested data on shigella infections reported to the responsible surveillance entities in 17 European countries. Reports of Sd1 from the published literature were then compared with Sd1 notified cases among European travellers from 1990 to 2002. Results Prior to a large epidemic in 1999-2000, no cases of Sd1 had been identified in West Africa. However, if travellers had been used as an early warning, Sd1 could have been identified in this region as earlier as 1992. Conclusion This project demonstrates that tracking diseases in European travellers could be used to detect emerging disease in developing countries. This approach should be further tested with a view to the continuous improvement of national health surveillance systems and existing European networks, and may play a significant role in aiding the international public health community to improve infectious disease control.